2020
DOI: 10.1108/jfmm-01-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Technology visibility and consumer adoption of virtual fitting rooms (VFRs): a cross-cultural comparison of Chinese and Korean consumers

Abstract: PurposeThe purpose of this study is to determine the influence of technology visibility and subsequent perceptions of VFRs on consumers' intention to adopt VFRs in the online shopping context. A cross-cultural comparison was conducted to examine the different relationships among technology visibility, consumer perceptions and adoption intentions between the Chinese and Korean consumers.Design/methodology/approachData were collected from 306 Chinese and 324 Korean consumers. The data were empirically analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
(124 reference statements)
3
13
0
Order By: Relevance
“…The findings are also in line with the literature in that with more immersive and realistic experiences offered by telepresence, consumers can better identify and facilitate the perceived utilitarian and hedonic value of shopping in AR-enhanced environments (Hou et al, 2019;Nikhashemi et al, 2021). This study also demonstrated positive influences of perceived utilitarian and hedonic values on consumers' adoption intention of AR-enhanced VTOs, affirming the integrative nature of consumer experiences that encompasses both cognitive and affective processing (Fiore & Kim, 2007;Lee, Xu, & Li, 2020).…”
Section: The Influence Of Technology Attributes On the Vto Adoption P...supporting
confidence: 87%
See 1 more Smart Citation
“…The findings are also in line with the literature in that with more immersive and realistic experiences offered by telepresence, consumers can better identify and facilitate the perceived utilitarian and hedonic value of shopping in AR-enhanced environments (Hou et al, 2019;Nikhashemi et al, 2021). This study also demonstrated positive influences of perceived utilitarian and hedonic values on consumers' adoption intention of AR-enhanced VTOs, affirming the integrative nature of consumer experiences that encompasses both cognitive and affective processing (Fiore & Kim, 2007;Lee, Xu, & Li, 2020).…”
Section: The Influence Of Technology Attributes On the Vto Adoption P...supporting
confidence: 87%
“…have not yet been exposed to VTOs particularly, in the United States compared with Eastern countries (e.g., China and Korea) (Lee, Xu, & Li, 2020), sensation-seeking tendency and technology anxiety were proposed in this study as having moderating effects on fashion consumers' adoption process of AR-enhanced VTOs.…”
Section: Personality Traitsmentioning
confidence: 99%
“…Previous research on consumer behavior around VFRs focused on the influence of perceived usefulness and ease‐of‐use (e.g., Huang & Qin, 2011; Kim & Forsythe, 2008), representing a relatively more utilitarian orientation. However, non‐utilitarian value is increasingly seen as important for explaining consumer adoption of VFRs, and this has been under investigation (Lee, Xu, & Li, 2020; Zhang et al., 2019). Using the desirability–feasibility framework, this study contributes to the literature by furthering the understanding of consumer behavior around VFRs, focusing on individual desirability and feasibility of using new technology rather than on characteristics of the new technology from the utilitarian perspective.…”
Section: Discussionmentioning
confidence: 99%
“…While participants perceived benefits of using VFRs, results of this study revealed consumer concerns with the feasibility of VFRs from both technical and personal perspectives. Previous research (e.g., Lee, Xu, & Li, 2020; Zhang et al., 2019) has partially addressed consumer concerns of using VFRs, typically with “perceived product risk” or “perceived privacy risk,” without taking a holistic view that clearly distinguishes concerns from the technical and personal perspectives. From the technical perspective, consumers were concerned about the accuracy of VFR‐suggested fit and security of personal information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation